ANALISIS FAKTOR YANG MENDASARI HARAPAN KONSUMEN TERHADAP ATRIBUT PRODUK BERAS - Kuswarini Kusno; Ronnie S. Natawidjaja; Lies Sulistyowati; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Many studies involving the measurement of rice attributes which are then analyzed to determine customer satisfaction have been carried out. In general, these measurements are carried out by researchers by determining the dimensions or constructs first. Whereas some of the attributes contained in a dimension or between these dimensions may be correlated with each other so that the results of consumer assessments can be biased. The city of Bandung has a relatively high level of rice consumption. The purpose of this study is to analyze the factors that underlie consumers in Bandung to assess the level of importance (expectations) of rice attributes. The research design is quantitative with survey research techniques to 108 respondents. Sampling using multistage sampling method. Primary data were analyzed by Exploratory Factor Analysis (EFA) method. The results showed that from the 14 variables of the importance of the rice attribute, 4 factors were formed that underlie consumer assessments of these attributes. Factor 1 contains 4 level of importance variables of rice attribute namely, the amount of beras kepala, habits, more filling, and easy to process. Factor 2 contains 6 level of importance variables of rice attributes, namely rice shape, whiteness, number of broken rice, groat content, rice grain length, and rice grain elongation. Factor 3 contains 3 level of importance variable namely, rice durability, affordable prices, and easy to obtain. Factor 4 contains the level of importance of the prestige attribute only. Information in the fourteen variables can be absorbed almost 66% by the four factors formed.